Constructive engagement in the interest of regional peace a critical reexamination of U.S. mediation in Southern Africa, 1981-1989 - Leslie, Alexis (Department of Political Studies, 2022)
This dissertation reexamines the negotiation process mediated by the U.S. that occurred between parties representing Angola, Cuba, Namibia, and South Africa during the 1980's. It presents the U.S. policy of constructive engagement ('81- '89) as a contributing factor in the mitigation of regional conflicts in Southern Africa. It reexamines whether the guiding principles of the mediation strategy effectively led to the Cuban withdrawal from Angola and the independence of Namibia. In addition, it looks at how constructive engagement created a regional climate for peace through the mitigation of these interconnected conflicts which significantly contributed to South Africa's transition away from apartheid. The central question of the dissertation is, did constructive engagement foster a regional climate for peace in Southern Africa, defined by the withdrawal of Cuban troops from Angola, the independence of Namibia, and a path towards South African democratization? There are three sub questions: (I) what were constructive engagements techniques and guiding principles? (II) why did the Reagan administration pursue the strategy; and (III) was constructive engagement a successful international conflict mediation strategy? To answer these questions, this dissertation will employ relevant literature to produce general principles of constructive engagement. It will use William Zartman and Saadi Touval's classifications of third-party mediators in international conflict in addition to Vincente Tome's staged model of the negotiation process. In this respect, this dissertation is an interpretative case study. This dissertation argues that constructive engagement is an effective conflict mediation strategy that made a significant impact on the propensity for peace in Southern Africa on several fronts. It aims is to reconsider the overwhelmingly negative opinion of U.S. intervention in Southern Africa throughout international relations discourse. It produces a piece of literature that explores the positive impact of the mediation strategy of constructive engagement as a driver for Southern African regional peace and subsequently a contributing factor in the end of apartheid.